1993
DOI: 10.1111/j.1528-1157.1993.tb05904.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal Status Epilepticus and Epilepsia Partialis Continua in Adults and Children

Abstract: Focal status epilepticus and epilepsia partialis continua (FSE-EPC) are most frequently seen with chronic focal progressive encephalitis of Rasmussen and Russian spring-summer encephalitis. FSE-EPC may be the presenting feature of nonketotic hyperglycemic diabetes mellitus but is more often noted as a late complication especially if there is a coexistent cerebral lesion such as cerebral infarction. FSE-EPC may be related to multiple sclerosis, primary or metastatic brain tumors, the MERRF-MELAS syndrome, benig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 40 publications
1
45
1
Order By: Relevance
“…Nonconvulsive SE and status limited to focal seizures are much less common (3)(4)(5). Except for series of patients with epilepsia partialis continua (EPC) (6,7) or simple partial seizures (5), most reports of focal SE are restricted to isolated cases or small series.…”
mentioning
confidence: 99%
“…Nonconvulsive SE and status limited to focal seizures are much less common (3)(4)(5). Except for series of patients with epilepsia partialis continua (EPC) (6,7) or simple partial seizures (5), most reports of focal SE are restricted to isolated cases or small series.…”
mentioning
confidence: 99%
“…In the present study, however, patients 1 and 3 showed no abnormal findings on routine MR sequences (including DWI) although pCASL results demonstrated abnormally increased CBF that correlated with EEG Pseudo Continuous Arterial Spin Labeling MR Imaging of Status Epilepticus � Minkyung Yi, et al (35,36). This increase in the metabolic workload is coupled with an increase in CBF during the early phase of SE (10,(35)(36)(37). Because of this compensation, the cellular energy state can be held at close to normal values (38).…”
mentioning
confidence: 71%
“…Seizures may be the result of T1DM patients' cerebrovascular complications that were commonly associated with varied types of brain damage (6). A possible relationship between cerebral infarction caused by diabetes mellitus and partial epilepsy has been also noted by Schomer et al (16). Diabetes mellitus can result in pathological capillary changes, leading to neurological complications, such as epilepsy (5).…”
Section: Discussionmentioning
confidence: 99%